The Endeavors of Islamic Religious Education Teachers to Cultivate Students' Spiritual Attitudes through the Practice of Dhuha Prayer at MI Ma'arif NU 5 Sekampung - Najah, Atin Nailatun; Aziz Q, Ikhwan; Wijaya, Adi (International Journal on Advanced Science, Education, and Religion, 2024)
Achieving successful learning goals for a teacher is something that is desired, especially forming students' spiritual attitudes that are better, always grateful, and closer to Allah SWT through worship. The aim of this researcher is to determine teacher Pai's efforts to shape students' spiritual attitudes through the habit of performing dhuha prayers at MI ma'arif NU 5 sekampung. The research method used in this research is qualitative research, with a qualitative descriptive approach. Then the data collection techniques are observation, interviews and documentation. Meanwhile, the data analysis technique has three stages, namely data reduction, data presentation, and drawing conclusions or verification. The results of the research show that the efforts made by PAI teachers in forming a spiritual attitude through getting used to the dhuha prayer, namely the dhuha prayer, went well where the teacher gave directions for carrying out the dhuha prayer which is usually done in prayer. The benefits and rewards are according to the level of rak'ah performed. Because there are still students who are difficult to get to pray Dhuha. There are several efforts made by Islamic religious education teachers to shape students' spiritual attitudes, namely by using four methods, namely the example method, discipline method, habituation method and advice method. So from this method it is hoped that teachers will always provide motivation to all students continuously. so that they are enthusiastic to always do something good. At first the teacher must use coercive methods so that students can understand that the teacher applies these methods with the aim of forming students' spiritual attitudes to be better than before. For this reason, students must realize that the teacher is doing this which will later be beneficial for the students themselves.